Influence of age on the pharmacokinetics, pharmacodynamics, efficacy, and safety of rivaroxaban. (2nd December 2018) - Moore, Kenneth T.; Wong, Peggy; Zhang, Liping; Pan, Guohua; Foody, JoAnne
Abstract: Objective: Atrial fibrillation, peripheral and coronary artery disease, and venous thromboembolism are major risk factors for stroke, disability, and death in the rapidly growing older (≥ 65 years.) population. In the absence of clear guidelines on the appropriate use of the newer non-vitamin K antagonist oral anticoagulants in this population, this study specifically reviews the available literature for rivaroxaban and the impact of age that may affect the pharmacokinetics, pharmacodynamics, efficacy, and safety of this anticoagulant. Methods: This review includes a summary of data obtained from the available literature concerning both older healthy subjects and older patients with various aspects of cardiovascular disease enrolled in rivaroxaban clinical trials and data from real world evidence studies. Results: Evaluation of the clinical pharmacology in healthy, older adults reveal no clinically relevant effect of age on rivaroxaban pharmacokinetics and pharmacodynamics. Population pharmacokinetic studies in older patients with thromboembolic diseases suggest a moderate effect of increasing age on rivaroxaban clearance, albeit not clinically significant. Additionally, sub-group analyses from large, phase 3 clinical trials demonstrate consistent efficacy and safety in the older patient population vs the overall population. These findings are further supported by real-world evidence studies. Conclusion: A favorable clinical profile with rivaroxaban was observed across age sub-groups, supporting the premise that dosing in older adults does not necessitate adjustment. However, it is prudent that a cautious and individualized approach is taken for treatment with any anticoagulant in older adults.